Acrylic plate with fluorescent function and preparation method thereof
By adding phosphor powder to the acrylic plate and introducing functional components such as modified glass fiber and nitrogen-containing graphene, the problems of poor fluorescence performance, low hardness and impact strength of acrylic plates are solved, and the comprehensive improvement of performance is achieved.
Patent Information
- Application Number
- CN202510282406.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing acrylic plates have problems such as poor fluorescence performance, low Shore hardness and low impact strength, which affect their actual use.
Add phosphors on the basis of methyl methacrylate, and functional components such as modified glass fibers and nitrogen-containing graphene are introduced to improve the fluorescence and mechanical properties of the material through high-temperature treatment and surface modification treatment.
The fluorescence function of acrylic plates is improved, while the Shore hardness and impact strength are improved, and the performance of practical applications is enhanced.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to an acrylic plate with a fluorescent function and a preparation method thereof. Background Art
[0002] Acrylic sheet, also known as plexiglass or PMMA (polymethyl methacrylate), is a transparent thermoplastic material; it has many advantages that inorganic glass does not have, such as excellent optical properties, acid and alkali resistance, good electrical insulation and biocompatibility, easy molding and processing, low relative density, high mechanical strength, etc., and is widely used in construction, manufacturing, aerospace, biomedicine and daily life. Acrylic sheet with fluorescent function is a special material. By adding fluorescent powder or fluorescent dye to the acrylic substrate, it can emit fluorescent effect when exposed to ultraviolet light or other light sources. This material is widely used in decoration, advertising, lighting and art design.
[0003] A Chinese patent (publication number CN114874367B) discloses a long afterglow luminous acrylic material and its preparation method. The invention is made of the following components in weight percentage: methyl methacrylate monomer 47-98%, photoinitiator 0.1-4%, thermal initiator 0.01-2%, inorganic long afterglow powder 1%-50%; by introducing a room temperature polymerization method, the long afterglow luminous powder can be stably dispersed in the methyl methacrylate prepolymer, and does not precipitate during the heating polymerization process, which effectively solves the problem of high difficulty in the production process of conventional long afterglow luminous acrylic. The long afterglow luminous acrylic produced by the present invention has a smooth appearance and excellent afterglow effect, and has a very considerable market prospect. However, the patent does not solve the problems of poor fluorescence performance, low Shore hardness and low impact strength of acrylic plates in the prior art, which seriously affects its actual use.
[0004] Therefore, how to add fluorescent powder to methyl methacrylate to achieve fluorescent function, and at the same time introduce functional components to improve Shore hardness and increase impact strength, has become a direction that needs to be focused on. Summary of the invention
[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide an acrylic sheet with fluorescent function and a preparation method thereof, aiming to solve the problems of poor fluorescence performance, low Shore hardness, and low impact strength of the acrylic sheet in the prior art.
[0006] The present invention adds fluorescent powder to methyl methacrylate to realize the fluorescent function, and introduces functional components such as modified glass fiber and nitrogen-containing graphene to prepare an acrylic plate with fluorescent function, while effectively improving the Shore hardness and increasing the impact strength.
[0007] The technical solution of the present invention is as follows: A first aspect of the present invention provides an acrylic plate with a fluorescent function. The composition comprises the following components by weight: 75-85 parts of methyl methacrylate, 0.2-0.4 parts of dibenzoyl peroxide, 10-20 parts of phosphor, 6-10 parts of glass fiber and 2-4 parts of graphene; The preparation method of the fluorescent powder comprises: dissolving 2 to 4 parts of urea in 20 to 30 parts of deionized water by weight, first adding 16 to 20 parts of 1 mol / L aluminum nitrate aqueous solution and 8 to 10 parts of 1 mol / L strontium nitrate aqueous solution, then adding 0.2 to 0.4 parts of 0.1 mol / L europium nitrate aqueous solution and 0.4 to 0.8 parts of 0.1 mol / L dysprosium nitrate aqueous solution, stirring for 30 to 40 minutes, and then performing a hydrothermal reaction to obtain a reaction product; mixing and grinding 10 to 20 parts of the reaction product and 1 to 2 parts of boric acid, and obtaining a powder A after high-temperature treatment; adding 10 to 20 parts of the powder A to 100 to 200 parts of anhydrous ethanol to disperse evenly, and then adding 1 to 3 parts of 3-aminopropyltriethoxysilane for surface treatment to obtain a fluorescent powder.
[0008] As a preferred technical solution of the present invention, the conditions of the hydrothermal reaction include: adjusting the pH to 4.4-4.8, stirring for 100-120 minutes, then hydrothermally reacting at 130-140°C for 12-16 hours, cooling to room temperature, filtering, washing with water, and drying.
[0009] As a preferred technical solution of the present invention, the conditions of the high temperature treatment include: a temperature of 1000-1100° C. and a time of 2-4 hours.
[0010] As a preferred technical solution of the present invention, the surface treatment conditions include: placing in a nitrogen atmosphere, adjusting the pH to 4.6-4.8, stirring at 60-70°C for 2-4 hours, cooling to room temperature after the reaction is completed, filtering, washing with anhydrous ethanol, and vacuum drying.
[0011] The strontium aluminate matrix material is formed in the phosphor by sintering, and provides an attachment carrier for europium ions and dysprosium ions. The europium ions emit visible light after absorbing the energy of the external light source, and the dysprosium ions can optimize the energy transfer efficiency and increase the luminous intensity. At the same time, the use of 3-aminopropyltriethoxysilane for treatment can reduce material surface defects, inhibit non-radiative recombination, and enhance the luminous intensity and afterglow time. The comprehensive effect improves the fluorescence performance of the acrylic board.
[0012] As a preferred technical solution of the present invention, the glass fiber is a modified glass fiber; The preparation method of the modified glass fiber comprises: adding 1-3 parts of polydimethyldiallylammonium chloride and 1-3 parts of sodium chloride to 800-1000 parts of deionized water to fully dissolve, then adding 2-4 parts of commercially available glass fibers for stirring treatment to obtain surface-treated glass fibers; dispersing 2-6 parts of nano-silicon dioxide in 800-1000 parts of deionized water to form a suspension, then adding 6-10 parts of glass fibers for coating treatment to obtain a glass fiber composite; mixing 90-130 parts of deionized water and 10-20 parts of anhydrous ethanol evenly, then adding 6-10 parts of the glass fiber composite for ultrasonic dispersion evenly, and then adding 1-3 parts of silane coupling agent KH-570 for modification treatment to obtain the modified glass fiber.
[0013] As a preferred technical solution of the present invention, the stirring treatment conditions include: stirring at a speed of 80-100 r / min for 20-30 min, washing with water, and drying.
[0014] As a preferred technical solution of the present invention, the coating treatment conditions include: stirring for 40 to 60 minutes, filtering, washing with water, and drying at 80 to 90° C. for 10 to 12 hours.
[0015] As a preferred technical solution of the present invention, the modification treatment conditions include: adjusting the pH to 4.2-4.6 with acetic acid, ultrasonication for 30-40 minutes, then mechanically stirring at 70-80°C for 60-80 minutes, centrifugal washing, and drying.
[0016] The nano-silica in the modified glass fiber is evenly covered on the surface of the glass fiber, forming a "bridge" to enhance the interfacial bonding force between the glass fiber and the acrylic matrix. When external force acts, the nano-silica can effectively transfer stress and reduce interfacial debonding. The enhanced interfacial bonding force enables the glass fiber to more effectively withstand external loads, thereby improving the overall hardness of the acrylic board.
[0017] As a preferred technical solution of the present invention, the graphene is nitrogen-containing graphene; The preparation method of the nitrogen-containing graphene comprises: dispersing 2 to 4 parts of commercially available graphene oxide in 800 to 1000 parts of deionized water, then adding 2 to 4 parts of urea, 1.6 to 2.4 parts of potassium hydroxide and 0.8 to 1.2 parts of potassium carbonate, mixing evenly and then performing doping treatment to obtain nitrogen-doped graphene; dissolving 10 to 12 parts of L-glutamic acid in 200 to 240 parts of sodium hydroxide solution with a mass concentration of 4 to 6% to obtain an L-glutamic acid mixed solution, adding 2 to 4 parts of the nitrogen-doped graphene to 600 to 800 parts of deionized water and dispersing evenly, then adding 200 to 240 parts of the L-glutamic acid mixed solution for stirring reaction to obtain nitrogen-containing graphene.
[0018] As a preferred technical solution of the present invention, the particle size D50 of the commercially available graphene oxide is 4-8 μm.
[0019] As a preferred technical solution of the present invention, the conditions of the doping treatment include: stirring at a speed of 60-80 r / min for 50-60 min, freeze-drying, then transferring to a tubular furnace, placing in a nitrogen atmosphere, calcining at 380-400° C. for 4-6 h, cooling to room temperature, washing with water, and vacuum drying.
[0020] As a preferred technical solution of the present invention, the stirring reaction conditions include: first ultrasonic dispersion for 20 to 30 minutes, then stirring for 20 to 24 hours under nitrogen protection, adding 100 to 120 parts of deionized water and 100 to 120 parts of anhydrous ethanol, centrifuging, washing with water, and drying.
[0021] Nitrogen-containing graphene introduces nitrogen atoms through urea. The lattice defects introduced by nitrogen atoms can pin dislocation movement and delay material fracture. At the same time, the two-dimensional layer structure of nitrogen-containing graphene forms a physical barrier in the composite material, hindering the expansion of cracks along the matrix direction, thereby effectively improving the impact strength of the acrylic plate.
[0022] A second aspect of the present invention provides a method for preparing an acrylic plate having a fluorescent function as described in the first aspect, comprising the following steps: Step S1: by weight, 75-85 parts of methyl methacrylate and 0.2-0.4 parts of dibenzoyl peroxide are mixed and stirred for 20-30 minutes, then reacted at 80-90° C. for 60-80 minutes, and cooled to room temperature to obtain a prepolymer; Step S2: In parts by weight, 10 to 20 parts of fluorescent powder, 6 to 10 parts of glass fiber and 2 to 4 parts of graphene are added to 75 to 85 parts of the prepolymer and stirred for 40 to 50 minutes, then transferred to a mold for heating and polymerization, cooled to room temperature, demolded, and polished to obtain an acrylic plate with fluorescent function.
[0023] As a preferred technical solution of the present invention, the conditions for the heating polymerization include: first heating at 65-70°C for 180-240 min, then heating at 75-80°C for 50-60 min, and finally heating at 100-105°C for 30-40 min.
[0024] Compared with the prior art, the present invention has the following beneficial effects: (1) The active amino group is introduced into the phosphor of the present invention through modification with 3-aminopropyltriethoxysilane, which can not only undergo addition reaction with the methacryloyloxy group of the silane coupling agent KH-570 in the modified glass fiber, but also combine with the carboxyl group on the surface of the nitrogen-containing graphene, thereby constructing a high-density network structure. On the one hand, the cross-linking points of the network structure restrict the movement of the polymer chain segments, making it more difficult for the material to deform under the action of external forces, thereby improving the Shore hardness. On the other hand, the network structure can block crack propagation and extend the crack path, thereby improving the impact resistance of the material. At the same time, the network structure containing the silane coupling treatment component can form a covalent bond with methyl methacrylate through the silane functional group, thereby reducing the defects inside the material and improving the fluorescence performance.
[0025] (2) In the phosphor of the present invention, a strontium aluminate matrix material is formed by sintering, and a carrier is provided for the attachment of europium ions and dysprosium ions, wherein europium ions emit visible light after absorbing energy from an external light source, and dysprosium ions can optimize energy transfer efficiency and increase luminous intensity. At the same time, treatment with 3-aminopropyltriethoxysilane can reduce surface defects of the material, inhibit non-radiative recombination, increase luminous intensity and afterglow time, and the combined effect improves the fluorescent properties of the acrylic plate.
[0026] (3) The nano-silica in the modified glass fiber of the present invention is evenly covered on the surface of the glass fiber, forming a "bridge" to enhance the interfacial bonding force between the glass fiber and the acrylic matrix. When external force acts, the nano-silica can effectively transfer stress and reduce the interfacial debonding phenomenon. The enhanced interfacial bonding force enables the glass fiber to more effectively withstand external loads, thereby improving the overall hardness of the acrylic board.
[0027] (4) The nitrogen-containing graphene of the present invention introduces nitrogen atoms through urea. The lattice defects introduced by the nitrogen atoms can pin dislocation movement and delay material fracture. At the same time, the two-dimensional layer structure of the nitrogen-containing graphene forms a physical barrier in the composite material, hindering the expansion of cracks along the matrix direction, thereby effectively improving the impact strength of the acrylic plate. DETAILED DESCRIPTION
[0028] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0029] The sources of some components in the embodiments and comparative examples are as follows: Methyl methacrylate, CAS No. 80-62-6, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Dibenzoyl peroxide, CAS No. 94-36-0, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Commercially available phosphor, model T42-015, purchased from Jiangmen Keheng Industrial Co., Ltd.; Commercially available glass fiber, product number S30527, was purchased from Shanghai Yuanye Biotechnology Co., Ltd.; Commercially available graphene oxide I, model SE1331, particle size D50 of 5 μm, purchased from Changzhou Sixth Element Materials Technology Co., Ltd.; Commercially available graphene oxide II, model SE1234, particle size D50 of 25 μm, purchased from Changzhou Sixth Element Materials Technology Co., Ltd.; Commercially available graphene oxide III, item number 1034343-98-0, particle size D50 of 0.6 μm, purchased from Shanghai Maoguo Nanotechnology Co., Ltd.; Urea, CAS No. 57-13-6, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Aluminum nitrate, CAS No. 7784-27-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Strontium nitrate, CAS No. 10042-76-9, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Europium nitrate, CAS No. 10031-53-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Dysprosium nitrate, CAS No. 10031-49-9, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Boric acid, CAS No. 10043-35-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.; 3-Aminopropyltriethoxysilane, CAS No. 919-30-2, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Polydimethyldiallylammonium chloride, CAS No. 26062-79-3, was purchased from Wuhan Jixinyibang Biotechnology Co., Ltd.; Sodium chloride, CAS No. 7647-14-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Nanosilica, product number S490064, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Silane coupling agent KH-570, product number S111153, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Potassium hydroxide, CAS No. 1310-58-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Potassium carbonate, CAS No. 584-08-7, was purchased from Sinopharm Chemical Reagent Co., Ltd.; L-Glutamic acid, CAS No. 56-86-0, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0030] Example 1 This embodiment provides a method for preparing an acrylic plate with a fluorescent function, comprising the following steps: Step S1: by weight, 85 parts of methyl methacrylate and 0.4 parts of dibenzoyl peroxide were mixed and stirred for 30 minutes, then reacted at 90° C. for 60 minutes, and cooled to room temperature to obtain a prepolymer; Step S2: In parts by weight, 20 parts of fluorescent powder, 10 parts of modified glass fiber and 4 parts of nitrogen-containing graphene are added to 85 parts of the prepolymer and stirred for 50 minutes, and then transferred to a mold for heating polymerization, first heated at 70°C for 180 minutes, then heated at 80°C for 50 minutes, and finally heated at 105°C for 30 minutes, cooled to room temperature, demolded, and polished to obtain an acrylic plate with fluorescent function.
[0031] Preparation of the fluorescent powder: by weight, 4 parts of urea are fully dissolved in 30 parts of deionized water, 20 parts of 1 mol / L aluminum nitrate aqueous solution and 10 parts of 1 mol / L strontium nitrate aqueous solution are first added, and then 0.4 parts of 0.1 mol / L europium nitrate aqueous solution and 0.8 parts of 0.1 mol / L dysprosium nitrate aqueous solution are added, stirred for 40 minutes, and then hydrothermally reacted, the pH is adjusted to 4.8, stirred for 120 minutes, and then hydrothermally reacted at 140°C for 12 hours, cooled to room temperature, and filtered. , washed with water, and dried to obtain a reaction product; 20 parts of the reaction product and 2 parts of boric acid were mixed and ground, and high-temperature treatment (temperature was 1100°C, time was 2h) was performed to obtain powder A; 20 parts of the powder A were added to 200 parts of anhydrous ethanol and dispersed evenly, and then 3 parts of 3-aminopropyltriethoxysilane were added for surface treatment, placed in a nitrogen atmosphere, adjusted to pH 4.8, stirred at 70°C for 2h, cooled to room temperature after the reaction was completed, filtered, washed with anhydrous ethanol, and vacuum dried to obtain a fluorescent powder.
[0032] Preparation of the modified glass fiber: by weight, 3 parts of polydimethyldiallylammonium chloride and 3 parts of sodium chloride are added to 1000 parts of deionized water to fully dissolve, then 4 parts of commercially available glass fiber are added for stirring treatment, stirred at a speed of 100r / min for 30 minutes, washed with water, and dried to obtain surface-treated glass fiber; 6 parts of nano-silicon dioxide are dispersed in 1000 parts of deionized water to form a suspension, then 10 parts of glass fiber are added for coating treatment, first stirred for 60 minutes, filtered, washed with water, and dried at 90°C for 10 hours to obtain a glass fiber composite; 130 parts of deionized water and 20 parts of anhydrous ethanol are mixed evenly, then 10 parts of the glass fiber composite are added for ultrasonic dispersion evenly, and then 3 parts of silane coupling agent KH-570 are added for modification treatment, the pH is adjusted to 4.6 with acetic acid, ultrasonicated for 40 minutes, then mechanically stirred at 80°C for 60 minutes, centrifugal washed, and dried to obtain the modified glass fiber.
[0033] Preparation of the nitrogen-containing graphene: 4 parts by weight of commercially available graphene oxide I (model SE1331, particle size D50 is 5 μm) are dispersed in 1000 parts of deionized water, and then 4 parts of urea, 2.4 parts of potassium hydroxide and 1.2 parts of potassium carbonate are added and mixed evenly for doping treatment, stirred at a speed of 80 r / min for 50 minutes, freeze-dried, and then transferred to a tube furnace, placed in a nitrogen atmosphere, calcined at 400° C. for 4 hours, cooled to room temperature, washed with water, and vacuum dried. , obtain nitrogen-doped graphene; dissolve 12 parts of L-glutamic acid in 240 parts of sodium hydroxide solution with a mass concentration of 6% to obtain an L-glutamic acid mixed solution, add 4 parts of the nitrogen-doped graphene to 800 parts of deionized water and disperse them evenly, then add 240 parts of the L-glutamic acid mixed solution to stir and react, first ultrasonically disperse for 30 minutes, then stir for 24 hours under nitrogen protection, add 120 parts of deionized water and 120 parts of anhydrous ethanol, centrifuge, wash with water, and dry to obtain nitrogen-containing graphene.
[0034] Example 2 This embodiment provides a method for preparing an acrylic plate with a fluorescent function, comprising the following steps: Step S1: by weight, 75 parts of methyl methacrylate and 0.2 parts of dibenzoyl peroxide were mixed and stirred for 20 minutes, then reacted at 80° C. for 80 minutes, and cooled to room temperature to obtain a prepolymer; Step S2: In parts by weight, 10 parts of fluorescent powder, 6 parts of modified glass fiber and 2 parts of nitrogen-containing graphene are added to 75 parts of the prepolymer and stirred for 40 minutes, and then transferred to a mold for heating polymerization, first heated at 65°C for 240 minutes, then heated at 75°C for 60 minutes, and finally heated at 100°C for 40 minutes, cooled to room temperature, demolded, and polished to obtain an acrylic plate with fluorescent function.
[0035] Preparation of the fluorescent powder: by weight, 2 parts of urea are fully dissolved in 20 parts of deionized water, 16 parts of 1 mol / L aluminum nitrate aqueous solution and 8 parts of 1 mol / L strontium nitrate aqueous solution are first added, and then 0.2 parts of 0.1 mol / L europium nitrate aqueous solution and 0.4 parts of 0.1 mol / L dysprosium nitrate aqueous solution are added and stirred for 30 minutes, and then a hydrothermal reaction is carried out, the pH is adjusted to 4.4, and stirred for 100 minutes, and then a hydrothermal reaction is carried out at 130° C. for 16 hours, cooled to room temperature, and filtered. The reaction product was washed with water and dried to obtain a reaction product; 10 parts of the reaction product and 1 part of boric acid were mixed and ground, and a powder A was obtained after high-temperature treatment (temperature was 1000°C, time was 4h); 10 parts of the powder A were added to 100 parts of anhydrous ethanol and dispersed evenly, and then 1 part of 3-aminopropyltriethoxysilane was added for surface treatment, placed in a nitrogen atmosphere, the pH was adjusted to 4.6, stirred at 60°C for 4h, cooled to room temperature after the reaction was completed, filtered, washed with anhydrous ethanol, and vacuum dried to obtain a fluorescent powder.
[0036] Preparation of the modified glass fiber: by weight, 1 part of polydimethyldiallylammonium chloride and 1 part of sodium chloride are added to 800 parts of deionized water to fully dissolve, then 2 parts of commercially available glass fibers are added for stirring treatment, stirred at a speed of 80r / min for 30 minutes, washed with water, and dried to obtain surface-treated glass fibers; 2 parts of nano-silicon dioxide are dispersed in 800 parts of deionized water to form a suspension, then 6 parts of glass fibers are added for coating treatment, first stirred for 40 minutes, filtered, washed with water, and dried at 80°C for 12 hours to obtain a glass fiber composite; 90 parts of deionized water and 10 parts of anhydrous ethanol are mixed evenly, then 6 parts of the glass fiber composite are added for ultrasonic dispersion evenly, and then 1 part of silane coupling agent KH-570 is added for modification treatment, the pH is adjusted to 4.2 with acetic acid, ultrasonicated for 30 minutes, then mechanically stirred at 70°C for 80 minutes, centrifuged and washed, and dried to obtain the modified glass fiber.
[0037] Preparation of the nitrogen-containing graphene: In parts by weight, 2 parts of commercially available graphene oxide I (model SE1331, particle size D50 is 5 μm) are dispersed in 800 parts of deionized water, and then 2 parts of urea, 1.6 parts of potassium hydroxide and 0.8 parts of potassium carbonate are added and mixed evenly, and then doped, stirred at a speed of 60 r / min for 60 min, freeze-dried, and then transferred to a tube furnace, placed in a nitrogen atmosphere, calcined at 3800° C. for 6 h, cooled to room temperature, washed with water, and vacuum dried. , obtain nitrogen-doped graphene; dissolve 10 parts of L-glutamic acid in 200 parts of sodium hydroxide solution with a mass concentration of 4% to obtain an L-glutamic acid mixed solution, add 2 parts of the nitrogen-doped graphene to 600 parts of deionized water and disperse them evenly, then add 200 parts of the L-glutamic acid mixed solution to stir and react, first ultrasonically disperse for 20 minutes, then stir for 20 hours under nitrogen protection, add 100 parts of deionized water and 100 parts of anhydrous ethanol, centrifuge, wash with water, and dry to obtain nitrogen-containing graphene.
[0038] Example 3 This embodiment provides a method for preparing an acrylic plate with a fluorescent function, comprising the following steps: Step S1: by weight, 80 parts of methyl methacrylate and 0.3 parts of dibenzoyl peroxide were mixed and stirred for 25 minutes, then reacted at 85° C. for 70 minutes, and cooled to room temperature to obtain a prepolymer; Step S2: In parts by weight, 15 parts of fluorescent powder, 8 parts of modified glass fiber and 3 parts of nitrogen-containing graphene are added to 80 parts of the prepolymer and stirred for 45 minutes, and then transferred to a mold for heating polymerization, first heated at 68°C for 220 minutes, then heated at 78°C for 55 minutes, and finally heated at 102°C for 35 minutes, cooled to room temperature, demolded, and polished to obtain an acrylic plate with fluorescent function.
[0039] Preparation of the fluorescent powder: by weight, 3 parts of urea are fully dissolved in 25 parts of deionized water, 18 parts of 1 mol / L aluminum nitrate aqueous solution and 9 parts of 1 mol / L strontium nitrate aqueous solution are first added, and then 0.3 parts of 0.1 mol / L europium nitrate aqueous solution and 0.6 parts of 0.1 mol / L dysprosium nitrate aqueous solution are added, stirred for 35 minutes, and then a hydrothermal reaction is carried out, the pH is adjusted to 4.6, stirred for 110 minutes, and then a hydrothermal reaction is carried out at 135°C for 14 hours, cooled to room temperature, filtered, and water is added. The reaction product was washed and dried to obtain a reaction product; 15 parts of the reaction product and 1.5 parts of boric acid were mixed and ground, and a powder A was obtained after high-temperature treatment (temperature was 1050°C, time was 3h); 15 parts of the powder A were added to 150 parts of anhydrous ethanol and dispersed evenly, and then 2 parts of 3-aminopropyltriethoxysilane were added for surface treatment, placed in a nitrogen atmosphere, adjusted to pH 4.7, stirred at 65°C for 3h, cooled to room temperature after the reaction was completed, filtered, washed with anhydrous ethanol, and vacuum dried to obtain a fluorescent powder.
[0040] Preparation of the modified glass fiber: by weight, 2 parts of polydimethyldiallylammonium chloride and 2 parts of sodium chloride are added to 900 parts of deionized water to fully dissolve, then 3 parts of commercially available glass fiber are added for stirring treatment, stirred at a speed of 90r / min for 25 minutes, washed with water, and dried to obtain surface-treated glass fiber; 4 parts of nano-silicon dioxide are dispersed in 900 parts of deionized water to form a suspension, then 8 parts of glass fiber are added for coating treatment, first stirred for 50 minutes, filtered, washed with water, and dried at 85°C for 11 hours to obtain a glass fiber composite; 110 parts of deionized water and 15 parts of anhydrous ethanol are mixed evenly, then 8 parts of the glass fiber composite are added for ultrasonic dispersion evenly, and then 2 parts of silane coupling agent KH-570 are added for modification treatment, the pH is adjusted to 4.4 with acetic acid, ultrasonicated for 35 minutes, then mechanically stirred at 75°C for 70 minutes, centrifuged and washed, and dried to obtain the modified glass fiber.
[0041] Preparation of the nitrogen-containing graphene: In parts by weight, 3 parts of commercially available graphene oxide I (model SE1331, particle size D50 is 5 μm) are dispersed in 900 parts of deionized water, and then 3 parts of urea, 1.9 parts of potassium hydroxide and 1.1 parts of potassium carbonate are added and mixed evenly, and then doped, stirred at a speed of 70 r / min for 55 minutes, freeze-dried, and then transferred to a tube furnace, placed in a nitrogen atmosphere, calcined at 390° C. for 5 hours, cooled to room temperature, washed with water, and vacuum dried. Obtain nitrogen-doped graphene; dissolve 11 parts of L-glutamic acid in 220 parts of sodium hydroxide solution with a mass concentration of 5% to obtain an L-glutamic acid mixed solution, add 3 parts of the nitrogen-doped graphene into 700 parts of deionized water and disperse them evenly, then add 220 parts of the L-glutamic acid mixed solution to stir and react, first ultrasonically disperse for 25 minutes, then stir for 22 hours under nitrogen protection, add 110 parts of deionized water and 110 parts of anhydrous ethanol, centrifuge, wash with water, and dry to obtain nitrogen-containing graphene.
[0042] Comparative Example 1 The difference between this comparative example and Example 1 is that commercially available phosphor (model T42-015) is used instead of the phosphor powder.
[0043] Comparative Example 2 The difference between this comparative example and Example 1 is that commercially available glass fiber (article number S30527) is used instead of the modified glass fiber.
[0044] Comparative Example 3 The difference between this comparative example and Example 1 is that graphene oxide I (model SE1331, particle size D50 is 5 μm) is used instead of nitrogen-containing graphene.
[0045] Comparative Example 4 The difference between this comparative example and Example 1 is that graphene oxide II (model SE1234, particle size D50 is 25 μm) is used instead of graphene oxide I (model SE1331, particle size D50 is 5 μm) to prepare nitrogen-containing graphene.
[0046] Comparative Example 5 The difference between this comparative example and Example 1 is that commercially available graphene oxide III (article number 1034343-98-0, particle size D50 is 0.6 μm) is used instead of graphene oxide I (model SE1331, particle size D50 is 5 μm) to prepare nitrogen-containing graphene.
[0047] The performance of the acrylic plates prepared in the above embodiments and comparative examples was tested, and the specific testing method is as follows: (1) Fluorescence performance test: The acrylic sheets prepared in the examples and comparative examples were excited for 10 min under a D65 standard light source (illuminance 1000 LX). The light source was removed and the 10-minute afterglow brightness and the total afterglow time when the visible brightness reached 0.3 mCd / m2 were measured.
[0048] (2) Shore hardness test: The test shall be conducted in accordance with the requirements of GB / T 2411-2008 Determination of indentation hardness (Shore hardness) of plastics and hard rubber using a durometer.
[0049] (3) Impact performance test: Test according to the requirements of GB / T 1043.1-2008 Determination of impact properties of simply supported beams of plastics Part 1: Non-instrumented impact test.
[0050] The above performance test data is shown in Table 1.
[0051] Table 1 Performance test results
[0052] From the above content, it can be seen that the present invention prepares acrylic plates with fluorescent functions (Examples 1 to 3) by adding fluorescent powder and introducing functional components such as modified glass fiber and nitrogen-containing graphene, and the overall performance is better.
[0053] Compared with Example 1, the fluorescent powder (model T42-015) was used to replace the fluorescent powder, and the fluorescent performance was worse, the Shore hardness was reduced, and the impact strength was reduced (Comparative Example 1); Compared with Example 1, the modified glass fiber (article number S30527) was used to replace the modified glass fiber, and the fluorescent performance was worse, the Shore hardness was reduced, and the impact strength was reduced (Comparative Example 2); Compared with Example 1, the nitrogen-containing graphene was replaced by graphene oxide I (model SE1331, particle size D50 is 5 μm), and the fluorescent performance was worse, the Shore hardness was reduced, and the impact strength was reduced (Comparative Example 3); Compared with Example 1, the graphene oxide II (model SE1234, particle size D50 is 25 μm) was used to replace graphene oxide I (model SE1331, particle size D50 was 5 μm) to prepare nitrogen-containing graphene. Since the particle size of graphene oxide II was too large and the modification effect was not good, the fluorescence performance deteriorated, the Shore hardness decreased, and the impact strength decreased (Comparative Example 4). Compared with Example 1, commercially available graphene oxide III (article number 1034343-98-0, particle size D50 was 0.6 μm) was used to replace graphene oxide I (model SE1331, particle size D50 was 5 μm) to prepare nitrogen-containing graphene. Since the particle size of commercially available graphene oxide III was too small and the modification effect was not good, the fluorescence performance deteriorated, the Shore hardness decreased, and the impact strength decreased (Comparative Example 5).
[0054] In summary, the present invention adds fluorescent powder to methyl methacrylate to achieve the fluorescent function, and introduces functional components such as modified glass fiber and nitrogen-containing graphene to prepare an acrylic plate with fluorescent function, while effectively improving the Shore hardness and increasing the impact strength.
Claims
1. An acrylic plate with fluorescent function, characterized in that: The composition comprises the following components by weight: 75-85 parts of methyl methacrylate, 0.2-0.4 parts of dibenzoyl peroxide, 10-20 parts of fluorescent powder, 6-10 parts of glass fiber and 2-4 parts of graphene; The preparation method of the fluorescent powder comprises: dissolving 2 to 4 parts of urea in 20 to 30 parts of deionized water by weight, first adding 16 to 20 parts of 1 mol / L aluminum nitrate aqueous solution and 8 to 10 parts of 1 mol / L strontium nitrate aqueous solution, then adding 0.2 to 0.4 parts of 0.1 mol / L europium nitrate aqueous solution and 0.4 to 0.8 parts of 0.1 mol / L dysprosium nitrate aqueous solution, stirring for 30 to 40 minutes, and then performing a hydrothermal reaction to obtain a reaction product; mixing and grinding 10 to 20 parts of the reaction product and 1 to 2 parts of boric acid, and obtaining a powder A after high-temperature treatment; adding 10 to 20 parts of the powder A to 100 to 200 parts of anhydrous ethanol to disperse evenly, and then adding 1 to 3 parts of 3-aminopropyltriethoxysilane for surface treatment to obtain a fluorescent powder.
2. The acrylic sheet with fluorescent function according to claim 1, characterized in that: The conditions of the hydrothermal reaction include: adjusting the pH to 4.4-4.8, stirring for 100-120 minutes, then hydrothermally reacting at 130-140° C. for 12-16 hours, cooling to room temperature, filtering, washing with water, and drying.
3. The acrylic sheet with fluorescent function according to claim 1, characterized in that: The conditions of the high temperature treatment include: a temperature of 1000-1100° C. and a time of 2-4 hours.
4. The acrylic sheet with fluorescent function according to claim 1, characterized in that: The surface treatment conditions include: placing under nitrogen atmosphere, adjusting the pH to 4.6-4.8, stirring at 60-70° C. for 2-4 hours, cooling to room temperature after the reaction is completed, filtering, washing with anhydrous ethanol, and vacuum drying.
5. The acrylic sheet with fluorescent function according to claim 1, characterized in that: The glass fiber is a modified glass fiber; The preparation method of the modified glass fiber comprises: adding 1-3 parts of polydimethyldiallylammonium chloride and 1-3 parts of sodium chloride to 800-1000 parts of deionized water to fully dissolve, then adding 2-4 parts of commercially available glass fibers for stirring treatment to obtain surface-treated glass fibers; dispersing 2-6 parts of nano-silicon dioxide in 800-1000 parts of deionized water to form a suspension, then adding 6-10 parts of glass fibers for coating treatment to obtain a glass fiber composite; mixing 90-130 parts of deionized water and 10-20 parts of anhydrous ethanol evenly, then adding 6-10 parts of the glass fiber composite for ultrasonic dispersion evenly, and then adding 1-3 parts of silane coupling agent KH-570 for modification treatment to obtain the modified glass fiber.
6. The acrylic sheet with fluorescent function according to claim 5, characterized in that: The coating treatment conditions include: stirring for 40-60 minutes, filtering, washing with water, and drying at 80-90° C. for 10-12 hours.
7. The acrylic sheet with fluorescent function according to claim 5, characterized in that: The modification treatment conditions include: adjusting the pH to 4.2-4.6 with acetic acid, ultrasonication for 30-40 minutes, mechanical stirring at 70-80° C. for 60-80 minutes, centrifugal washing, and drying.
8. The acrylic sheet with fluorescent function according to claim 1, characterized in that: The graphene is nitrogen-containing graphene; The preparation method of the nitrogen-containing graphene comprises: dispersing 2 to 4 parts of commercially available graphene oxide in 800 to 1000 parts of deionized water, then adding 2 to 4 parts of urea, 1.6 to 2.4 parts of potassium hydroxide and 0.8 to 1.2 parts of potassium carbonate, mixing evenly and then performing doping treatment to obtain nitrogen-doped graphene; dissolving 10 to 12 parts of L-glutamic acid in 200 to 240 parts of sodium hydroxide solution with a mass concentration of 4 to 6% to obtain an L-glutamic acid mixed solution, adding 2 to 4 parts of the nitrogen-doped graphene to 600 to 800 parts of deionized water and dispersing evenly, then adding 200 to 240 parts of the L-glutamic acid mixed solution to carry out stirring reaction to obtain nitrogen-containing graphene; The particle size D50 of the commercially available graphene oxide is 4-8 μm.
9. The acrylic sheet with fluorescent function according to claim 1, characterized in that: The doping treatment conditions include: stirring at a speed of 60-80 r / min for 50-60 min, freeze drying, then transferring to a tubular furnace, placing in a nitrogen atmosphere, calcining at 380-400° C. for 4-6 h, cooling to room temperature, washing with water, and vacuum drying.
10. A method for preparing an acrylic plate with fluorescent function as claimed in claims 1 to 9, characterized in that: The steps include: Step S1: by weight, 75-85 parts of methyl methacrylate and 0.2-0.4 parts of dibenzoyl peroxide are mixed and stirred for 20-30 minutes, then reacted at 80-90° C. for 60-80 minutes, and cooled to room temperature to obtain a prepolymer; Step S2: In parts by weight, 10 to 20 parts of fluorescent powder, 6 to 10 parts of glass fiber and 2 to 4 parts of graphene are added to 75 to 85 parts of the prepolymer and stirred for 40 to 50 minutes, then transferred to a mold for heating and polymerization, cooled to room temperature, demolded, and polished to obtain an acrylic plate with fluorescent function.
Citation Information
Patent Citations
A long-afterglow luminescent acrylic material and its preparation method
CN114874367B
Carboxyl-modified functionalized graphene quantum dot as well as preparation method and application thereof
CN112938953A
Ultrasonic-assisted method for preparing europium-dysprosium co-doped strontium aluminate fluorescent powder
CN113105889A
High-flame-retardant photoelectric composite cable sheath material with good processability and preparation method thereof
CN114409997A
Long-afterglow luminous acrylic material and preparation method thereof
CN114874367A